Gender and Income Tax Compliance Among Small and Medium Enterprises in Uganda - Otai, Isaac Peter (Journal of Economics and Business Aseanomics, 2023)
This study sought to examine the association between gender and income tax compliance amongst sole proprietorship SMEs in the district of Soroti, Uganda. Literature was reviewed as directed by the specific objectives. The study was supported by the benefit theory and the Fischer tax compliance model. The study adopted the explanatory and descriptive research designs. The study picked 384 participants from the target population of 2,590 owners of SMEs. Data was gathered using questionnaires and analyzed using cross tabulation and inferential statistics. Hypotheses were tested at 5 percent significance and normality test conducted. Study findings disclosed that gender has insignificant relationship with filing of returns of income tax and prompt discharge of income tax. The study concluded that gender differences do not explain decisions of owners of SMEs to file returns of income tax and pay income tax promptly. The study recommended that policy makers should consider demographic background of individual taxpayers in mapping out strategies to improve individual income tax compliance.